From the Debate on the Legality of Waqf al-Ahlī to its Implementation in Southeast Asia: Indonesia, Malaysia, and Singapore - Pirmani, Ulfa; Kurniawan, Edi; Najmi (NAJAHA, 2024)
The debate on the heresy of waqf al-ahlī (family endowment) in the early 20th century significantly impacted its legality in Muslim countries. In Southeast Asia, with samples from Indonesia, Malaysia, and Singapore, they followed the majority opinion of ulama. They implemented it in the law to improve the management of waqf al-ahlī. This paper examines the legality of waqf al-ahlī from the perspective of fiqh and the Law and its implementation model in the three countries through extensive literature study. The results reveal that the debate on the legality of waqf al-ahlī is more influenced by socio-economic and political factors and misunderstandings about the purpose of waqf rather than theological considerations. Therefore, most Muslim scholars recognise this type of waqf, and it is implemented by most Muslim countries, including the three countries that are the objects of this study. Comparative analysis shows that Singapore achieves higher productivity and efficiency in managing waqf al-ahlī than Indonesia and Malaysia. These findings refute the view of waqf al-ahlī as heresy and emphasise the importance of good governance, a comprehensive legal framework, and efficient management to optimise the potential of waqf al-ahlī as an instrument of sustainable socio-economic development.